2009
DOI: 10.1152/ajprenal.90703.2008
|View full text |Cite
|
Sign up to set email alerts
|

Rho-kinase inhibition reduces pressure-mediated autoregulatory adjustments in afferent arteriolar diameter

Abstract: Preglomerular resistance is regulated by calcium influx- and mobilization-dependent mechanisms; however, the role of Rho-kinase in calcium sensitization in the intact kidney has not been carefully examined. Experiments were performed to test the hypothesis that Rho-kinase inhibition blunts pressure-mediated afferent arteriolar autoregulatory behavior and vasoconstrictor responses evoked by angiotensin II and P2X1 receptor activation. Rat kidneys were studied in vitro using the blood-perfused juxtamedullary nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 73 publications
(126 reference statements)
6
35
0
Order By: Relevance
“…44 L-VDCCs play a prominent role in controlling RBF and GFR by maintaining basal renal vascular tone and regulating preglomerular microvascular responses to various vasoconstrictor stimuli. [23][24][25][26]45,46 Thus, the involvement of L-VDCCs in S1P-mediated vasoconstriction of preglomerular microvessels implies that S1P may play an important role in regulating renal vascular resistance and in controlling the renal microcirculation. Nevertheless, a small proportion of S1P-mediated afferent arteriolar vasoconstriction was retained in the presence of diltiazem or nifedipine, suggesting that other intracellular signaling pathways may also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…44 L-VDCCs play a prominent role in controlling RBF and GFR by maintaining basal renal vascular tone and regulating preglomerular microvascular responses to various vasoconstrictor stimuli. [23][24][25][26]45,46 Thus, the involvement of L-VDCCs in S1P-mediated vasoconstriction of preglomerular microvessels implies that S1P may play an important role in regulating renal vascular resistance and in controlling the renal microcirculation. Nevertheless, a small proportion of S1P-mediated afferent arteriolar vasoconstriction was retained in the presence of diltiazem or nifedipine, suggesting that other intracellular signaling pathways may also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting- Calcium measurements were performed using fura 2. Data were modified from an earlier report [74] ly, the afferent arteriolar vasoconstriction elicited by α β-methylene ATP was completely eliminated [88]. Thus, P2 receptor activation involves induction of a number of second messenger systems that also play major roles in regulating pressure-dependent renal perfusion.…”
Section: P2 Receptors and The Renal Microcirculation: Single Vessel Smentioning
confidence: 98%
“…Inhibition of Rho-kinase in hydronephrotic kidneys vasodilates virtually every pre-and postglomerular artery/arteriole and attenuates endothelin-or adenosine-induced renal microvascular vasoconstriction [87]. Similarly, preliminary in vitro studies revealed that Rho-kinase inhibition with Y-27632 produced a rapid, concentration-dependent afferent arteriolar vasodilation and inhibited renal autoregulatory responses [88]. In addition, vasoconstrictor responses induced by angiotensin II or ATP were markedly attenuated [88].…”
Section: P2 Receptors and The Renal Microcirculation: Single Vessel Smentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using local administration of inhibitors in intact rats have reported ROCK inhibitor-induced dose-dependent increases renal blood flow (Bauer and Parekh, 2003;Cavarape et al, 2003b). At the glomerular level, measurements utilizing videomicroscopy in isolated split rat hydronephrotic kidneys or the in vitro blood-perfused juxtamedullary nephron technique have determined that ROCK inhibitors induce predominantly afferent and lesser efferent, arteriolar dilation (Cavarape et al, 2003b;Nakamura et al, 2003;Inscho et al, 2009). In the present studies, the whole kidney haemodynamic pattern induced by ROCK inhibitors in diabetic rats suggests not only afferent but also an important efferent effect of these compounds in diabetic rats.…”
Section: Figurementioning
confidence: 99%